2018
DOI: 10.3350/cmh.2018.0006
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of synbiotic and sitagliptin versus sitagliptin alone in patients with nonalcoholic fatty liver disease

Abstract: Background/AimsNon-alcoholic fatty liver disease (NAFLD) is one of the most prevalent chronic liver diseases in recent years. The aim of this study was to evaluate the effects of sitagliptin with and without a synbiotic supplement in the treatment of patients with NAFLD.MethodsIn total, 138 NAFLD patients aged 18-60 years were enrolled in the study. Patients were randomized to one of the following treatments for 16 weeks: Group I (n=68), sitagliptin 50 mg daily plus placebo (one capsule per day) or group II (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 38 publications
(34 reference statements)
2
31
0
Order By: Relevance
“…One study evaluated a synbiotic as an adjunctive treatment to metformin, where both the intervention and control groups received metformin (36). Another study evaluated a synbiotic as an adjunctive treatment to sitagliptin, where both the intervention and control groups received sitagliptin (40).…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One study evaluated a synbiotic as an adjunctive treatment to metformin, where both the intervention and control groups received metformin (36). Another study evaluated a synbiotic as an adjunctive treatment to sitagliptin, where both the intervention and control groups received sitagliptin (40).…”
Section: Included Studiesmentioning
confidence: 99%
“…The effect of probiotics/synbiotics on BMI was assessed in 12 studies (778 participants), of which 3 evaluated probiotics (21-23, 27) and 9 evaluated synbiotics (30)(31)(32)(33)(34)(35)(36)(37)40). Pediatric studies were excluded from analyses examining changes in BMI.…”
Section: Bmimentioning
confidence: 99%
“…In animal models of NAFLD, both glucagon‐like peptide‐1 receptor agonists (GLP‐1Ras) and dipeptidyl peptidase‐4 inhibitor (DPP‐IVi) improve many pathways linked to steatohepatitis, although their efficacy at the clinical level has been mixed (see Tables and ). In open‐label prospective trials, sitagliptin has been found to improve plasma aminotransferases, IHTG, and liver histology . But negative results have also been reported with sitagliptin in open‐label studies and in all three placebo‐controlled trials .…”
Section: Effect Of Sitagliptin In Nafldmentioning
confidence: 99%
“…In the current issue, Sayari et al [ 16 ] conducted a randomized, double-blind, controlled trial to evaluate the effect of a combination of sitagliptin, an anti-diabetic drug by inhibiting DPP-4, with synbiotic compared to sitagliptin alone in NAFLD patients with obesity (body mass index 25 or more) and impaired fasting blood glucose. Sixty-eight patients were assigned to the sitagliptin plus synbiotic group and seventy patients were assigned to the sitagliptin alone group.…”
mentioning
confidence: 99%
“…Their study showed that the combination of sitagliptin with synbiotic improved asparate aminotransferase ( P =0.018) and metabolic parameters, including fasting blood glucose ( P <0.001), cholesterol ( P <0.029), and low-density lipoprotein ( P <0.001) levels more than sitagliptin therapy alone. The study of Sayari et al revealed significant effects of synbiotic therapy on NAFLD patients through a randomized placebo-controlled trial [ 16 ]. Although gut microbiota-related mechanisms involved in the development of NAFLD have been elucidated and many experimental studies have been reported, clinical studies are insufficient.…”
mentioning
confidence: 99%